Widening Spectrum of a Reversible Splenial Lesion with Transiently Reduced Diffusion - Takanashi, J; Barkovich, A.J; Shiihara, T; Tada, H; Kawatani, M; Tsukahara, H; Kikuchi, M; Maeda, M (American Journal of Neuroradiology, 2006)
Four patients with encephalitis/encephalopathy and parenchymal lesions accompanying reversible splenial lesions were retrospectively evaluated. In 3 patients, reversible lesions with transiently reduced diffusion were seen in the splenium and symmetrically in the peripheral frontoparietal white matter, clinical signs and symptoms were mild, and recovery was complete. These and previous observations suggest a less severe course and outcome for patients with reversible lesions isolated to the splenium or to the splenium and peripheral frontoparietal white matter.